PI3k/AKT signaling pathway: Erythropoiesis and beyond - Jafari, Mahjoobeh; Ghadami, Elham; Dadkhah, Tahereh; Akhavan‐Niaki, Haleh (Journal of cellular physiology, 2019)
Erythropoiesis is a multi‐step process that involves the differentiation of hematopoietic stem cells into mature red blood cells (RBCs). This process is regulated by several signaling pathways, transcription factors and microRNAs (miRNAs). Many studies have shown that dysregulation of this process can lead to hematologic disorders. PI3K/AKT is one of the most important pathways that control many cellular processes including, cell division, autophagy, survival, and differentiation. In this review, we focus on the role of PI3K/AKT pathway in erythropoiesis and discuss the function of some of the most important genes, transcription factors, and miRNAs that regulate different stages of erythropoiesis which play roles in differentiation and maturation of RBCs, prevention of apoptosis, and autophagy induction. Understanding the role of the PI3K pathway in erythropoiesis may provide new insights into diagnosing erythrocyte disorders. PI3K/AKT signaling pathway regulates erythropoiesis through specific transcription factors and microRNAs (miRNAs). PI3K/AKT signaling pathway is critical for survival, proliferation, and differentiation of erythroid cells.